Denegação e desidentidade: a metaficção historiográfica em Nove noites, de Bernardo Carvalho - Sakai, Luiz Guilherme Fernandes da Costa (2013)
This study discusses the identity construction and interpellation in Brazilian contemporary literature through historical novel and historiographical metafiction, concepts studied by Györg Lukács and Linda Hutcheon, respectively. These two subgenres reveal a relation that is different from the truthful events in which the novel is based. The historical novel, emerged in 19th century, uses them to attest their fictional verisimilitude, and in the national context, it has joined the taskwork to build a Brazilian identity. The historiographical metafiction, which emerged in the second half of 20th century, uses the truthful events to question, destabilize and rewrite them. Nove noites, from the author Bernardo Carvalho, gets close to this second subgenre. However, a survey of Carvalho s critical fortune has indicated a supposed inverisimilitude trace in his literary production; this discovery questions not only the historical speech, but also the fiction itself. From this starting point, our study is going to investigate, especially in the chosen novel, the bounds between fiction and reality (linked to history) and identity and non-identity in a dialog with the historical novel and the historiographical metafiction. Presenting also Carvalho s critical production, it s evident in this research that he appreciates an experimental and inventive fiction, and denies trends and common sense in relation to literature. Therefore, this research challenges the hypothesis that, by one side, Nove noites has some historiographical metafiction characteristics and points out to a non-identity dimension, concept used by Italo Moriconi to define the crisis in which the Latin-American thought has been facing in this globalized scenery. In the other hand, when he destabilizes his own construction of sense, he overacts the subgenre in which he was primarily associated and strengthen, in another level, the position the writer registers in this critical texts